Endotoxin-Effects of Vaccination with Escherichia coli Vaccines in the Pig - Garcia, P. (Acta Vet Scand, 1998)
Endotoxins from Gram-negative bacteria have been shown to be potent biological activators and are involved in many pathological reactions (Yagoda et al. 1990). Since endotoxins are ubiquitous compounds, they can create serious problems for the pharmaceutical industry. There are several examples of unavoidable drug contamination and of endotoxins that cannot be removed from recombinant procedures involving Escherichia coli bacteria (Yagoda et al. 1990). It is difficult to establish a true threshold dose at which endotoxins will cause clinical effects, but doses less than or equal to 3 ng/kg body weight (bw) can cause fever, chills and headache in humans (Elin et al. 1981). Another reference gives 5 endotoxin units (EU)/kg bw for similar clinical symptoms (Anon. 1987). Vaccines prepared using E. coli bacteria have a high potential for endotoxin content. This is important because endotoxin contamination in general can distort analyses of pharmacological studies and produce unpredictable and erratic effects on animals that receive contaminated vaccines. It is therefore important to identify possible effects of endotoxin-containing vaccines on various physiologic endpoints. It is also pertinent to assess the magnitude of any potential risks involved in using such vaccines. The purpose of this study was to evaluate the blood chemical and clinical response of castrated young boars to commercially available vaccines to E. coli where the bacteria have been formaldehyde killed and the endotoxins have not been removed.